Postsynaptic density radiation signature following space irradiation - Impey, Soren; Pelz, Carl; Riparip, Lara-Kirstie; Tafessu, Amanuel; Fareh, Fatema; Zuloaga, Damian G.; Marzulla, Tessa; Stewart, Blair; Rosi, Susanna; Turker, Mitchell S.; Raber, Jacob (Frontiers in Physiology, 2023)
The response of the brain to space radiation is an important concern for astronauts during space missions. We assessed the response of the brain to 28Si ion irradiation (600 MeV/n), a heavy ion present in the space environment, on cognitive performance and whether the response is associated with altered DNA methylation in the hippocampus, a brain area important for cognitive performance. At 0.3 Gy, but not at 0.6 Gy or 0.9 Gy, 28Si ion irradiation impaired cognition that correlated with altered gene expression and 5hmC profiles that mapped to specific gene ontology pathways. Comparing hippocampal DNA hydroxymethylation following proton, 56Fe ion, and 28Si ion irradiation revealed a general space radiation synaptic signature with 45 genes that are associated with profound phenotypes. The most significant categories were glutamatergic synapse and postsynaptic density. Thus, the brain’s response to space irradiation involves novel excitatory synapse and postsynaptic remodeling.